(3QSGdI aj efGaY GdSahaGJs
(3ChdgG (B:s
(3Saha GdHRhQ , ef cJGH SGHhQ GdfGaY ef faN GdeYOI , hjWQO GdQjGM s
(3BNQgG (B:s
(3Saha BNQ fGaY (B( (3ef GdNabGJ hRdb GdeYOI , hGdQWhHGJ GddRLI(B) (3jDNP hRf hQO CQHYI OQGge WHGTjQ efg OQgekG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B357 - (3U(B366s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B112 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B((3O (B532) s
Keywords: (3GdWHs